1978
DOI: 10.1007/bf01981534
|View full text |Cite
|
Sign up to set email alerts
|

Detection of chrysanthemum stunt and potato spindle tuber viroids by polyacrylamide gelelectrophoresis

Abstract: Stunt viroid can be detected in chrysanthemums with the polyacrylamide gelelectrophoresis (PAGE) method developed by Morris and Smith (1977) for potato spindle tuber viroid. The time of sample preparation can even be shortened considerably. The reliability of the short and the complete PAGE method proved to be similar to that of the biological 'Mistletoe' test in a parallel experiment. Combined samples can be tested in the complete PAGE method easily permitting the detection of one diseased chrysanthemum top i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Due to the fact that viroids have very low molecular weights, polyacrylamide gel electrophoresis (PAGE) was first used to detect viroid RNAs [63,64]. Molecular method to detect and quantify CSVd RNA in infected plants based on hybridization assays, where the viroid RNA hybridized to a 32 P-labeled cDNA of CSVd, were also developed [65,66].…”
Section: Detection Methodsmentioning
confidence: 99%
“…Due to the fact that viroids have very low molecular weights, polyacrylamide gel electrophoresis (PAGE) was first used to detect viroid RNAs [63,64]. Molecular method to detect and quantify CSVd RNA in infected plants based on hybridization assays, where the viroid RNA hybridized to a 32 P-labeled cDNA of CSVd, were also developed [65,66].…”
Section: Detection Methodsmentioning
confidence: 99%
“…Extraction of PSTV was according to the method of Morris and Smith (1977) modified by Mosch et al (1978).…”
Section: Methodsmentioning
confidence: 99%
“…Attempts to detect the occurrence of viroids were made according to the methods of Morris and Smith (1977) and Mosch et al (1978). Attempts to purify a tumour-inducing virus were performed with tumours from N. christii, N. clevelandii, N. megalosiphon, and N. rustica using differential and density-gradient centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…Using polyacrylamide-gel electrophoresis methods which can successfully detect potato spindle tuber and chrysanthemum stunt viroids (Morris and Smith, 1977;Mosch et al, 1978) no viroid could be found in tumours. Using polyacrylamide-gel electrophoresis methods which can successfully detect potato spindle tuber and chrysanthemum stunt viroids (Morris and Smith, 1977;Mosch et al, 1978) no viroid could be found in tumours.…”
Section: Isolation Of Bacteriamentioning
confidence: 99%